(3QSGdI SQ GdbOQs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3SCd HYV GdfGS GdTjN GdQFjS CHj Ydi Hf SjfG Yf eYfi bhd GdUhajI ef YQa SQ GdbOQ s
(3BNQgG (B:s
(3dGf GdfGS jfHZi Gf jchf ebjOjf HGMO bjOjf GeG HbjO GdTQY hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdSGOS hGdKdGKhfs
(3GfXQg eY GdeNWhW Qbe (B292 (3ef faS GdHYKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs